Magnitude and Predictors of Post-cesarean Surgical Site Infection in Enugu, Southeast Nigeria - Nnagbo, Johnpaul E.; Ugwu, George O.; Matthew, Eze I.; Obi, Samuel N.; Agu, Polycarp U.; Nnagbo, Chinonso L.; Ugwu, Emmanuel O.; Nwagha, Ifeanyi U. (Nigerian Journal of Basic and Clinical Sciences, 2024)
ContextPost-cesarean surgical site infection (SSI) is one of the leading causes of maternal morbidity and mortality. It is speculated that there is an increasing incidence of post-cesarean SSI above that reported value a decade ago, especially as the cesarean section (CS) rate and concern for antibiotics resistance increase in Nigeria.AimTo determine the incidence and predictors of post-cesarean SSI at the University of Nigeria Teaching Hospital (UNTH) Ituku/Ozalla and Enugu State University of Science and Technology Teaching Hospital (ESUT-TH) Parklane, Enugu.Settings and DesignProspective cohort study comprising 160 consenting pregnant women who consented to have a CS at the UNTH and ESUT-TH.Material and MethodsEligible patients who consented to elective and emergency CS were included, but those with clinical chorioamnionitis were excluded. Surgery was performed by senior resident physicians and consultants in OBGYN using similar surgical and postoperative protocols. Participants were followed up until 30 days postdelivery to identify those who developed SSI.Statistical AnalysisStatistical analysis was performed using IBM SPSS software version 20.0 (Armonk, NY). The Chi-square test was used to test the association between qualitative variables, while logistic regression was used to determine the predictors of postoperative SSI. The significance level was established at P < 0.05.ResultThe incidence of post-cesarean SSI in this study was 13.7%. Maternal booking body mass index ≥30 and postoperative hemoglobin
Keywords: Infection; post-cesarean; surgical site